Financing marine conservation from restructured debt: a case study of the Seychelles - Booth, Mara; Brooks, Cassandra M. (Frontiers in Marine Science, 2023)
In the face of the threats posed to the oceans by a changing climate, the need for marine conservation programs grows rapidly. Scaling with this need, demands sufficient funding to support ambitious conservation projects. This funding must be obtained from increasingly varied and innovative sources since private grants and government allocated funds has proved insufficient. Debt-for-nature swaps are a financial mechanism seeking to improve debt burden while setting up environmental programs. This method of debt restructuring has existed for decades, but is seeing a resurgence of use and interest in recent years. Here we present an exploratory case study of a Seychelles debt-for-nature swap which examines this financial mechanism’s ability to fund impactful conservation projects, particularly in marine Economic Exclusion Zones (EEZ) of Small Island Developing States (SIDS). The focus on SIDS is vital because they are extraordinarily predisposed to climate change consequences and tend to have economies which lack resilience to exogenous shocks. The Seychelles finalized a conversion of their sovereign debt with Paris Club creditors and The Nature Conservancy as a broker in 2015 with the goal of creating a robust marine spatial plan. They received notable recognition for multiple novel aspects of this deal as well as the sheer scale of the marine space protected (400,000 sq. km), and thus serves as a robust case study to analyze if debt-for-nature swaps have evolved since its theoretical conception in 1984. Our research favors qualitative data by employing a case study approach which draws on semi-structured interviews with key informants, content analysis of online resources, and a literature review. This research suggests that while the model has yet to be cemented, the Seychelles case study is representative of a coming evolution in debt-for-nature swap practices. By examining the critical governance factors that were employed in the Seychelles, this research reveals key takeaways for future implementation and establishing national candidacy. The findings highlight debt status relative to the economy, political willpower, funding streams utilized, and the use of co-production practices.